Pengaruh Current Ratio, Return on Equity dan Debt to Equity Ratio Terhadap Stock Price (Pada Perusahaan Healthcare Sub Sektor Pharmaceuticals and Healthcare Research di Bursa Efek Indonesia Periode Tahun 2015 – 2023) - Komalasari, Nenden; Syarif, Devyanthi (Sekretariat Pusat Lembaga Komunitas Informasi Teknologi Aceh, 2025)
Finding out how the Current Ratio, Return on Equity, and debt-to-equity ratio affect Stock Price is the goal of this study (in healthcare companies in the pharmaceuticals and healthcare research subsector on the Indonesia Stock Exchange for the Period 2015–2023). This study employed a quantitative research methodology that combines a descriptive and verifying approach. Quantitative information in the form of financial statements (annual reports) from the annual reports of manufacturing companies in the food and beverage subsector listed on the Indonesia Stock Exchange for the years 2017–2023 was utilized to gather secondary data. The partial testing findings indicated that the Debt to Equity Ratio has an impact on the Stock Price, whereas the Current Ratio and Return on Equity have no effect. The Stock Price is simultaneously impacted by the Debt to Equity Ratio, Return on Equity, and Current Ratio, according to the results of the simultaneous testing.